Perbandingan Warisan Islam dan Warisan Nasional - Muhari Muhari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the comparison between Islamic inheritance law and national inheritance law (KUHPerdata) within the framework of legal pluralism in Indonesia. The research aims to analyze the differences, similarities, and practical implementation of both legal systems in inheritance distribution. The method employed is normative legal research using a statutory approach and a comparative literature review of relevant legal sources, regulations, and scholarly works. The findings reveal that Islamic inheritance law is determinative, as the distribution of inheritance shares is explicitly prescribed in the Qur'an and Hadith, whereas national inheritance law under the Civil Code provides greater flexibility by allowing heirs and testators to determine inheritance distribution through wills. In practice, many Indonesian families adopt a combination of these two legal systems, particularly by utilizing pre-inheritance grants to achieve equitable outcomes while respecting religious and legal considerations. These findings demonstrate that legal pluralism plays a significant role in shaping inheritance practices in Indonesia, reflecting the coexistence and interaction of religious and national legal frameworks in contemporary society.